STUDY OF INFRARED SPECTROSCOPY OF MgZnXTiXFe2-2XO4 SPINEL FERRITE SYSTEMS - S.V.KSHIRSAGAR; MAHESHMALKAR, P.R.; MAULAGE, S.B.; JADHAV, K.M (Innovare Journal of Sciences, 2020)
Objectives: Infrared spectroscopy is the method of choice of qualitative analysis of organic material and it has wide application to inorganic substances as well. The infrared spectrum of a material has aptitude for the fingerprint, a unique property of that material and of its physical state. Materials and methodology: The samples of MgZnxTixFe2-2xO4spinel ferrite systems with varying x [x = 0.0, 0.1, 0.2, 0.3, 0.4, 0.5 and 0.6] were synthesized by double sintering ceramic method. A.R. grade oxides of magnesium, zinc, titanium and ferric were used for the preparation of MgZnxTixFe2-2xO4 ferrite [1]. The infrared spectra of all the samples of the present series were recorded at room temperature in the range 200 cm-1- 1000cm-1 on a Perkin Elemer spectrometer (Model 783). Results: The spectra have been used to identify the band positions. Two prominent bands are seen in the IR spectra. The high frequency band ν1 is seen to be in the range 592 to 620 cm-1 and the lower frequency band ν2 is in the range 427 to 425 cm-1. Conclusion: Two prominent absorption bands are seen in the IR spectra, which is the characteristic feature of spinel ferrite. Debye temperature obtained from IR data increases with composition ‘x’.